2005
DOI: 10.1161/01.hyp.0000161880.59963.da
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Combined Angiotensin-Converting Enzyme Inhibition and Angiotensin Receptor Blockade in Hypertension

Abstract: Abstract-Some evidence suggests that long-term angiotensin-converting enzyme (ACE) inhibition may become less effective, thereby increasing angiotensin II levels, which could be inhibited by the addition of an angiotensin receptor blocker. We conducted a meta-analysis of randomized trials with searches of MEDLINE, EMBASE, and Cochrane databases. Overall, the combination of an ACE inhibitor and an angiotensin receptor blocker reduced ambulatory blood pressure by 4.7/3.0 mm Hg (95% confidence interval [CI], 2.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 35 publications
2
107
0
3
Order By: Relevance
“…Moreover, a substudy of the main trial using 24-h ambulatory monitoring demonstrated that those with the greatest reductions in proteinuria at 6 mo had the slowest declines in GFR, an effect independent of BP level achieved (14). The notion that the combination of an ACE inhibitor and an ARB should be used only for proteinuric renal disease and not for BP reduction is supported further by the results of a clinical trial and by a meta-analysis of studies that used the combination (33,34).…”
Section: Proteinuria Reduction and Kidney Disease Progressionmentioning
confidence: 99%
“…Moreover, a substudy of the main trial using 24-h ambulatory monitoring demonstrated that those with the greatest reductions in proteinuria at 6 mo had the slowest declines in GFR, an effect independent of BP level achieved (14). The notion that the combination of an ACE inhibitor and an ARB should be used only for proteinuric renal disease and not for BP reduction is supported further by the results of a clinical trial and by a meta-analysis of studies that used the combination (33,34).…”
Section: Proteinuria Reduction and Kidney Disease Progressionmentioning
confidence: 99%
“…46,47 Combination therapy may, however, reduce albuminuria by 30-40% compared to monotherapy with either drug. 47 Pending the results of additional clinical trials, combination therapy with an ACE inhibitor and ARB is not currently recommended.…”
Section: Potential Reduction In Modificationmentioning
confidence: 99%
“…22,23 Currently, it is unclear whether the combination of an ACE inhibitor with an ARB, provides greater renoprotection than the use of either approach alone. 24 The COOPERATE trial combined an ACE inhibitor and an ARB and demonstrated an additional 30% reduction in proteinuria over either agent alone, an effect independent of blood pressure. 25,26 This implies an additive effect of these agents that is specific to the intrarenal RAAS.…”
Section: Introductionmentioning
confidence: 99%